JUSTIFICATION OF PRIORITIES FOR ACTIVATION OF SMALL AND MEDIUM BUSINESSES INNOVATIVE DEVELOPMENT - HORODNYTSKYI, Roman (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The characteristics are summarized and the requirements composition for the management support of the small and medium-sized businesses innovative development activation is specified. The essence of the enterprise individual dynamic capabilities is determined as a prerequisite for choosing priorities for the small and medium-sized businesses innovative development activation. It is proven that the peculiarities of the innovations inherent in a particular enterprise choice and implementation are business individual dynamic capabilities manifestation, which formation becomes a key element in creating original competitive advantages for the business entity. The features of the strategic planning process implementation in the field of small and medium-sized businesses innovative development activating are determined (the ensuring subject area coverage breadth achievement of the business entity strategic goals; impact of the innovative solutions adaptive nature on supporting the enterprise strategic flexibility in the increasing volatility context of the business environment; the determining vagueness of the optimal option for implementing innovative changes from the available wide set of available alternatives for innovative development; implementing innovative solutions effectiveness multi-criteria assessment in the context of insufficient certainty of the production and technological system prospects for the transformation of the changes in the business entity market opportunities. It is proven that the prerequisites for choosing strategic choice priorities in the field of determining the prospects for implementing innovative solutions are determined by the cumulative impact of the state combination assessments factors for the business competitive advantages formation (manufacturer market positions in the target market; the resource base efficiency using for development; financial and investment opportunities for implementing innovative projects) in the enterprise forming the innovative flexibility context. The economic essence definition is clarified and a description of the enterprise’s innovation policy elements is proposed.